Agricultural Absentee Land Ownership Rules: Problem or Solution for Farmers on Food Resilience Program? - Perkasa, Surya Rimba; Koeswahyono, Imam; Masykur, Mohammad Hamidi (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2024)
Abstract: Food resilience is a critical aspect of national sustainability programs. with large and diverse population, Indonesia needs to prioritize food resilience as a primary focus of government programs. Empowering Indonesia's predominantly farming population is one way to achieve food resilience. In this regard, the government can utilize absentee land to achieve food resilience goals and improve the welfare of farmers. However, regulations restricting land ownership to civil servants under Article 3 of Government Regulation No. 224 of 1961 hinder the utilization of absentee land. These regulations pose a significant obstacle to farmers who seek to engage in or expand agricultural endeavors. The conflicts arising from these regulations constitute the most substantial barrier to farmers' efforts to realize food resilience programs in Indonesia. This research uses a normative legal research method, focusing on the absent land through statutory and case approaches. The results of this research suggest that absentee land regulations are no longer relevant given the current state of affairs, as they impede the maximization of food resilience, particularly for farmers in the agricultural sector. Keywords: Absentee Land, Farm Land, Food Resilience